Use of traditional, complementary and alternative medicine in nine countries: A cross-sectional multinational survey - Bo-Young Youn; Seunghwan Moon; Kyungyul Mok; Chunhoo Cheon; Youme Ko; Sunju Park; Bo-Hyoung Jang; Yong Cheol Shin; Seong-Gyu Ko (Elsevier, 2022)
Objectives: Traditional, complementary, and alternative medicine (TC&AM) play an exceptional role in health care around the world as many patients has sought a holistic approach. Setting: In this study, a multinational survey was developed and administered to obtain experience, attitude, and promotion information with regard to the international use of TC&AM among nine countries: Germany, United States, Japan, China, Malaysia, Vietnam, Russia, Kazakhstan, and United Arab Emirates (UAE). The survey was administered via online to members of SurveyMonkey Audience, a proprietary panel of respondents who were recruited from a diverse population worldwide. Results: A total of 1071 participants has completed the survey. The participants were in favor of the treatments and therapies as well as expressed positive attitudes and also have used herbal medicine treatment more than acupuncture therapy and also used the modalities to promote metabolism rather than treating musculoskeletal diseases. Moreover, participants mentioned that TC&AM should be applied for treating and managing infectious diseases, such as COVID-19. Additionally, participants recommended using Facebook channel to promote its treatments and therapies. Conclusion: Based on the results, this study provides initial insights on TC&AM that may influence the non-users globally and perhaps inspire a need for further research including more countries in different continents.